Phylogenetic characterization of two novel Kamalomyces species in Tubeufiaceae (Tubeufiales) - Rungtiwa Phookamsak (2018)
© 2017 German Mycological Society and Springer-Verlag GmbH Germany, part of Springer Nature Two novel species of bambusicolous fungi in the genus Kamalomyces, collected from northern Thailand, are described and illustrated herein. Kamalomyces bambusicola and K. thailandicus spp. nov. are typical of the genus Kamalomyces (Tubeufiaceae, Tubeufiales) and are morphologically distinct from known species with respect to their size of ascomata, asci and ascospores, ascospore septation and peridium structure, including the subiculum comprising hyphae on the host surface. Morphological examination reveals that the asexual morph of K. bambusicola is associated with its sexual morph in a subiculum forming dictyochlamydosporous conidia, which are similar to the asexual morph of Chlamydotubeufia. Phylogenetic analyses of combined LSU, ITS and TEF1-α sequence data also support these two species as distinct and confirm their phylogenetic affinities within the Tubeufiaceae. In particular, Kamalomyces shares a close phylogenetic relationship to Helicoma.